MANAJEMEN PESERTA DIDIK DI LEMBAGA PENDIDIKAN ISLAM SMA PLUS YASPIDA - Zahra Putria Ayuni Assyamsudin; Wiwi Wiguna; Adi Rosadi (ADIBA : JOURNAL OF EDUCATION, 2025)
Student management is very important and is also the most important foundation and integrated process in the management of educational institutions, including aspects of development and administration. The approach used in this research is qualitative research. The method used is a qualitative descriptive method with research in the form of observation, interviews and document study. The location of this research was SMA Plus Yaspida Sukabumi. Inspections of school principals, deputy principals and teachers in infrastructure development including planning and implementation are carried out. In the world of education, curriculum is important and very important because without the right curriculum, students will not be able to achieve the right learning goals. As time goes by, in the world of education, the curriculum changes and everything changes to suit students' needs, so we hope that based on the results and discussion above students can adapt well. Jaspida High School has a built-in curriculum program and assessment and learning planning system that is similar to school exams.